The Major Risk Factors of Cerebral Stroke in Patients Admitted To The Hospitals of North West Bank Districts - Ahmed Juma Ibrahim Ali (My University, 2002)
A retrospective study was aimed at assess the major risk factors of cerebral stroke in the North West Bank districts hospitals. The study included 522 cases of cerebral stroke that were admitted to the hospitals, during the year 1/1/2000 to 31/12/2000. Data collected from the medical records about risk factors, laboratory tests, brain CT reports, family history, and drugs before admission and smoking. The patients were classified into ischemic stroke, hemorrhagic stroke, and no apparent lesion and not available (not done or not found). The outcomes of cerebral stroke were by using discharge report. The study results showed that the most common risk factors of cerebral stroke were hypertension, previous stroke, diabetes mellitus, a trial fibrillation, myocardial infarction and transient ischemic attack. Other risk factors include family history and increase blood level sugar, platelets, cholesterol and packed cell volume. The study recommends further studies, on primary prevention of risk factors and medical follow up.

A retrospective study was aimed at assess the major risk factors of cerebral stroke in the North West Bank districts hospitals. The study included 522 cases of cerebral stroke that were admitted to the hospitals, during the year 1/1/2000 to 31/12/2000. Data collected from the medical records about risk factors, laboratory tests, brain CT reports, family history, and drugs before admission and smoking. The patients were classified into ischemic stroke, hemorrhagic stroke, and no apparent lesion and not available (not done or not found). The outcomes of cerebral stroke were by using discharge report. The study results showed that the most common risk factors of cerebral stroke were hypertension, previous stroke, diabetes mellitus, a trial fibrillation, myocardial infarction and transient ischemic attack. Other risk factors include family history and increase blood level sugar, platelets, cholesterol and packed cell volume. The study recommends further studies, on primary prevention of risk factors and medical follow up.
The Major Risk Factors of Cerebral Stroke in Patients Admitted To The Hospitals of North West Bank Districts